THE RHETORICAL ORGANIZATION OF CHINESE AND AMERICAN STUDENTS’ EXPOSITORY ESSAYS: A CONTRASTIVE RHETORIC STUDY - Yang, Lin; Cahill, David (International Journal of English Studies, 2008)
A widespread assumption in the contrastive rhetoric field is the linearity/circularity dichotomy which suggests that Chinese writing is characterized by indirection. This study examines to what extent Chinese university students’ writing differs from that of American students. A total of 200 expository essays (50 by American university students in English, 50 by Chinese students in Chinese, and 100 by beginning and advanced English learners in English) were analyzed. Results indicate that Chinese students, like their U.S. counterparts, also prefer directness in text and paragraph organization, but generally U.S. students tend to be significantly more direct than Chinese students. An examination of modern Chinese writing manuals found that Chinese rhetoricians also encourage directness in structuring expository essays. These findings point to a need for greater awareness of the similarities between writing in “contrasting” languages.